Contribuição aos estudos da gestão dos resíduos sólidos urbanos no Pontal do Paranapanema - MANOEL, Agessander (2019)
This dissertation contributes to the debate on the management of solid urban waste because it understands that the environmental issue deals with the disproportionate use of natural resources to meet basic human needs, as well as the destination of waste caused by their production and consumption. The problem that guided this research was to recognize the challenges of municipal solid waste management from the institution of the National Policy on Solid Waste by Law 12,305 / 10. Thus, the research seeks to understand the reality and the practices adopted to confront waste management, taking as a parameter the municipalities of Álvares Machado -SP, Pirapozinho - SP, Presidente Prudente - SP and Tarabai - SP because of their distinct characteristics and because they present analysis potential in the Pontal do Paranapanema region. The hypothesis adopted was that the municipalities would not be prepared for the adjustments and deadlines required by Law 12,305 / 10. The general objective was to discuss the challenges of solid urban waste management, confronting the legislation discussed with the historical reality on the management of solid urban waste, using as example the selected municipalities. Thus, in the course of the research the issue of unsustainability of current production and consumption patterns was addressed through a chronology of interrelated events and discussed the management and management of solid waste through official data. The methodology used was applied research, using the field research, qualitative approach and the method was the deductive. The techniques employed were the interview and the unsystematic observation. As a result, it was verified that the situation of solid urban waste management in the municipalities studied presents several difficulties, such as insufficient funds, lack of human resources with the necessary skills and lack of planning. It is evident in this research that most municipalities are not prepared to adapt to the National Solid Waste Policy within the period expected by the Law, and that social debate is the great tool to minimize the challenges proposed by legislators